2018
DOI: 10.1007/s00223-018-0474-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Bone Mineral Density in HIV Newly Diagnosed Therapy-Naive Patients Without Any Secondary Causes of Osteoporosis

Abstract: Bone loss and vitamin D deficiency are common in HIV patients. However, bone health status in newly diagnosed HIV patients has not been thoroughly described. Our aim was to assess the bone mineral density (BMD), bone resorption and vitamin D status in newly diagnosed HIV patients. A prospective observational study in HIV newly diagnosed therapy-naive persons. Patients with secondary causes of osteoporosis were excluded. Bone densitometry (DXA), a bone resorption marker (CTx), 25-hydroxyvitamin D (25OHD), CD4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
12
0
2
Order By: Relevance
“…In this sense, Paccou J et al (12) involving 49 naïve men, mean age was 31.6 ( 7.7) years demonstrated that the prevalence of low BMD was 24.5% 95% CI, 13.3-38.9 , similar to our ndings. In another study by Ceballos et al (11) involving 70 naïve men, mean age 31 years (19-50), Low BMD (Z-score < -2.0) was found in 13% of the patients.…”
Section: Discussionmentioning
confidence: 89%
“…In this sense, Paccou J et al (12) involving 49 naïve men, mean age was 31.6 ( 7.7) years demonstrated that the prevalence of low BMD was 24.5% 95% CI, 13.3-38.9 , similar to our ndings. In another study by Ceballos et al (11) involving 70 naïve men, mean age 31 years (19-50), Low BMD (Z-score < -2.0) was found in 13% of the patients.…”
Section: Discussionmentioning
confidence: 89%
“…In this sense, Paccou J et al [ 12 ] involving 49 naïve men, mean age was 31.6 (±7.7) years demonstrated that the prevalence of low BMD was 24.5% [95% CI, 13.3–38.9], similar to our findings. In another study by Ceballos et al [ 11 ] involving 70 naïve men, mean age 31 years (19–50), Low BMD (Z-score < − 2.0) was found in 13% of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…Our purpose is to provide information on bone situation in antiretroviral-therapy–naïve HIV-infected adult male under 50 years of age. It is expected that study participants will have the presence of an increased bone involvement than similar uninfected population, even prior to initiation of ART and under 50 years [ 11 , 12 ], which could suggest the beginning of the bone study prior to 50 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vitamin D may have a crucial role in bone osteoporosis, which may be essential in migrants and individuals with HIV infection [39][40][41][42][43]. Child neglect cases discovered in forensic practice and unpublished cases debated only in courts may represent the tip of an iceberg [29,44].…”
Section: Vitamin Dmentioning
confidence: 99%